Is there a processing advantage for verb-noun collocations in Chinese reading? Evidence from eye movements during reading - Li, Hui; Wang, Xiaolu; Paterson, Kevin B.; Zhang, Hua; Li, Degao (Frontiers in Psychology, 2023)
A growing number of studies show a processing advantage for collocations, which are commonly-used juxtapositions of words, such as "joint effort" or "shake hands", suggesting that skilled readers are keenly perceptive to the occurrence of two words in phrases. With the current research, we report two experiments that used eye movement measures during sentence reading to explore the processing of four-character verb-noun collocations in Chinese, such as 修改文章 ("revise the article"). Experiment 1 compared the processing of these collocations relative to similar four-character expressions that are not collocations (e.g., 修改结尾, "revise the ending") in neutral contexts and contexts in which the collocation was predictable from the preceding sentence context. Experiment 2 further examined the processing of these four-character collocations, by comparing eye movements for commonly-used "strong" collocations, such as 保护环境 ( "protect the environment"), as compared to less commonly-used "weak" collocations, such as 保护自然 ( "protect nature"), again in neutral contexts and contexts in which the collocations were highly predictable. The results reveal a processing advantage for both collocations relative to novel expressions, and for "strong" collocations relative to "weak" collocations, which was independent of effects of contextual predictability. We interpret these findings as providing further evidence that readers are highly sensitive to the frequency that words co-occur as a phrase in written language, and that a processing advantage for collocations occurs independently of contextual expectations.